2022
DOI: 10.1186/s12891-022-05015-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting spine–femur discordance in the percentage of young adult mean on dual-energy X-ray absorptiometry in the elderly population: a retrospective study

Abstract: Background Several retrospective studies have reported spine–femur discordance in bone mineral density (BMD) values. However, the average age of individuals in these studies was the mid-50s, which is younger than the typical age of individuals requiring treatment for primary osteoporosis. Therefore, we aimed to investigate factors associated with discordance in the percentage of young adult mean (YAM) between the lumbar spine and femoral neck in the elderly population. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Today, POP is the most common form of osteoporosis due to natural aging [ 3 , 4 ]. The latest seventh national population census of China [ 5 ] showed that the country has the largest absolute number of older person in the world, at 260 million and 190 million aged above 60 and 65, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Today, POP is the most common form of osteoporosis due to natural aging [ 3 , 4 ]. The latest seventh national population census of China [ 5 ] showed that the country has the largest absolute number of older person in the world, at 260 million and 190 million aged above 60 and 65, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evidence links exposure to such chemicals with heightened susceptibility to endocrine disorders and chronic ailments [10], as well as discernible impacts on bone health [11,12]. Furthermore, it is worth noting that while a correlation exists between BMD across various skeletal regions, discrepancies can arise between BMD measurements in the lumbar spine and the hip, giving rise to divergent classi cations of bone loss, commonly referred to as spine-femur BMD discordances [13]. These discordances can result in certain individuals with osteoporosis not receiving appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%